Comparison of Sensitivity and Specificity between Tuberculin Skin Test (TST) and Interferon-Gamma Release Assays (IGRA) for Latent TB Infection (LTBI) in Household Contacts of Drug-Sensitive TB Patients in Medan - Rina Sundari; Bintang Yinke Magdalena Sinaga; Delores Elisabeth Sormin; Arlinda Sari Wahyuni (Jurnal Impresi Indonesia, 2025)
Latent Tuberculosis Infection (LTBI) is a condition characterized by the absence of clinical symptoms of active disease, yet it carries the risk of progressing to active tuberculosis (TB), particularly within the first two years following infection. The diagnosis of LTBI relies on immunological tests, such as the Tuberculin Skin Test (TST) and Interferon-Gamma Release Assays (IGRA), each with its own strengths and limitations. To compare the sensitivity and specificity of TST and IGRA in the diagnosis of LTBI in household contacts of drug-sensitive TB patients in Medan. This study is an analytical observational study with a cross-sectional design involving 105 subjects who were household contacts of drug-sensitive TB patients. All subjects underwent chest X-ray, TST, IGRA, and Xpert MTB/RIF examination when indicated. Data were statistically analyzed using the Chi-Square test. Among 105 participants, 93 did not have pulmonary TB. Of 93 subjects, 24.7% tested positive by TST and 32.3% by IGRA. TST's calculated sensitivity and specificity compared to IGRA were 76.7% and 63.5%, respectively. TST demonstrates lower sensitivity and specificity than IGRA in diagnosing LTBI. However, TST remains a valuable screening tool, particularly in resource-limited settings.